Hubungan pengungkapan diri dengan pemaafan pada remaja - Nada De Audry; Alifah Nabilah Masturah (Fakultas Psikologi, 2023)
Forgiveness to others can be given when self-disclosure has been made. This study aims to determine the relationship between self-disclosure and forgiveness in adolescents. The research design uses a non-experimental quantitative type of correlational study. Subjects were 199 high school (SMA) youth and equivalent. The sampling technique uses accidental sampling. The measuring tool uses the Conceptualizing and Measuring Self-Disclosure scale and the Transgression-Related Interpersonal Motivation scale (TRIM-18). Results Analysis of the data using Spearman's rho showed a negative relationship between self-disclosure and forgiveness (r=-0.487; p<0.001). This means that adolescents who are more open in expressing themselves will tend to find it more difficult to forgive others. Thus, explaining oneself broadly and deeply is done by adolescents because they have not forgiven other people who are in conflict with them. Keywords: Adolescences, forgiveness, self-disclosure